First-line pembrolizumab in patients with advanced non-small cell lung cancer and high PD-L1 expression: real-world data from a Spanish multicenter study - Piedra, Aida; Martínez-Recio, Sergio; Hernández, Ainhoa; Morán, Teresa; Arriola, Edurne; Recuero-Borau, Jordi; Cobo, Manuel; Cordeiro, Patricia; Mosquera, Joaquín; Fernández, Manuel; García-Campelo, Rosario; Calles, Antonio; et al. (Frontiers in Oncology, 2024)
IntroductionPembrolizumab stands as a first-line option for patients with advanced non-small cell lung cancer (NSCLC) and high programmed death-ligand 1 (PD-L1) expression (PD-L1 ≥50%). Several factors such as antibiotic exposure, low body mass index (BMI), certain metastatic location or poor performance status may influence outcomes.MethodsWe conducted a multicenter retrospective analysis in a cohort of patients with advanced high PD-L1 expression NSCLC treated with first-line pembrolizumab in clinical practice. We sought to evaluate clinical outcomes according to several factors.ResultsAmong the 494 included patients, median age was 67.29 years, 77% were male, 54% and 38% were former or current smokers, respectively; 84% had an Eastern Cooperative Oncology Group (ECOG) Performance Status (PS) of 0-1, and 48% had a BMI of <25. 32% of patients had bone metastases, 32% brain metastases and 16% liver metastases. 35% of patients had exposure to antibiotics (AB), 44% to corticosteroids and 62% to proton pump inhibitors (PPi). With a median follow-up of 14.3 months, the median overall survival (OS) and progression-free survival (PFS) were 15.9m (95% CI 13.1 to 18.8) and 9.9m (95% CI 7.7 to 12.1), and the overall response rate (ORR) was 43%. After univariate analysis, median OS in patients with ECOG-PS 0 vs. 1 vs. 2 was 36.7m vs. 14.8m vs. 2.7m (p<0.001). Median OS in patients who received treatment with corticosteroids vs. patients without exposure was 11.4m vs. 22.3m (p<0.001). After multivariate analysis, corticosteroid exposure (HR 1.41) and ECOG-PS (HR 2.40) maintained a prognostic impact.DiscussionFirst-line pembrolizumab outcomes in advanced high PD-L1 expression NSCLC patients could be negatively influenced by corticosteroid exposure or poor ECOG-PS.